TERMINAL FLOWER‐1/CENTRORADIALIS inhibits tuberisation via protein interaction with the tuberigen activation complex. (14th July 2020) - Zhang, Xing; Campbell, Raymond; Ducreux, Laurence J. M.; Morris, Jennifer; Hedley, Pete E.; Mellado‐Ortega, Elena; Roberts, Alison G.; Stephens, Jennifer; Bryan, Glenn J.; Torrance, Lesley; Chapman, Sean N.; Prat, Salomé; et al.
SUMMARY: Potato tuber formation is a secondary developmental programme by which cells in the subapical stolon region divide and radially expand to further differentiate into starch‐accumulating parenchyma. Although some details of the molecular pathway that signals tuberisation are known, important gaps in our knowledge persist. Here, the role of a member of the TERMINAL FLOWER 1 / CENTRORADIALIS gene family (termed StCEN ) in the negative control of tuberisation is demonstrated for what is thought to be the first time. It is shown that reduced expression of StCEN accelerates tuber formation whereas transgenic lines overexpressing this gene display delayed tuberisation and reduced tuber yield. Protein–protein interaction studies (yeast two‐hybrid and bimolecular fluorescence complementation) demonstrate that StCEN binds components of the recently described tuberigen activation complex. Using transient transactivation assays, we show that the StSP6A tuberisation signal is an activation target of the tuberigen activation complex, and that co‐expression of StCEN blocks activation of the StSP6A gene by StFD‐Like‐1. Transcriptomic analysis of transgenic lines misexpressing StCEN identifies early transcriptional events in tuber formation. These results demonstrate that StCEN suppresses tuberisation by directly antagonising the function of StSP6A in stolons, identifying StCEN as a breeding marker to improve tuber initiation and yield through the selection of genotypes with reduced StCEN expression. Significance Statement: Understanding the mechanism of tuber initiation in potato provides a key route to increasing productivity of a crop that is essential for food security. We demonstrate that a member of the potato phosphatidylethanolamine‐binding protein gene family ( StCEN ) is a key component in the regulation of tuberisation that acts via interaction with the tuberigen activation complex to regulate early tuberisation transcriptional changes.